Culture Shock (Cultural Show) of Lampung Students in Yogyakarta - Albi Mahennaro; Angga Intueri Mahendra P. (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Culture shock is a feeling where a person feels pressured or shocked when faced with a new culture and environment. The purpose of this study was to find out the causes of culture shock and the adaptation process of Lampung students in Yogyakarta in dealing with culture shock. This study used a qualitative descriptive method with the object of research namely the culture shock of Lampung students in Yogyakarta and took 4 sources from Lampung. Data collection used in this study used in-depth and semi-structured interviews to obtain complete results and information for research needs. The results of this study indicate that the cause of the culture shock process in Lampung students in Yogyakarta comes from within oneself and the environment. As well as the adaptation of Lampung students in Yogyakarta is very diverse. Judging from the existence of cultural adaptation actions carried out by Lampung students in Yogyakarta as an overseas place.